EXPLORING THE RELATIONSHIP BETWEEN PLACE ATTACHMENT AND YOUTH’S INVOLVEMENT IN RICE FIELD ACTIVITIES - Samsudin, Puteri Yuliana; Mohd Arshard, Wan Nur Rukiah (PLANNING MALAYSIA, 2024)
Youth’s experience, knowledge and values in relation to rice field activities play an important role in motivating the youth to get involved in these activities. However, there is a lack of research that focuses on the relationship between place attachment and activity involvement. The aim of this paper is to explore the relationship between place attachment and rural youth’s involvement in rice field activities. Three homestays in Kedah were selected as case studies and quantitative (302 questionnaires) approaches were applied to achieve the objective. The questionnaire survey was conducted among youth aged 20 - 34 years old. Major findings in this study include a positive relationship between place attachment and youth activity involvement. Youth who have knowledge, experience, and values in relation to rice field activities are inclined to be involved in homestay activities. The findings of this study contribute to the theories regarding youth activity involvement and place attachment. It is suggested that practitioners in built environment, tourism planning and landscape planning as well as parents should help to encourage the youth to get involved in rice field activities in homestay programmes and in their daily lives.